A comprehensive review of the anticancer effects of decursin - Chu, Yueming; Yuan, Qiang; Jiang, Hangyu; Wu, Liang; Xie, Yutao; Zhang, Xiaofen; Li, Lin (Frontiers in Pharmacology, 2024)
Cancer is a globally complex disease with a plethora of genetic, physiological, metabolic and environmental variations. With the rising resistance to current anticancer drugs, efforts have been made to develop effective cancer treatments. Currently, natural products are considered promising cancer therapeutic agents due to their potent anticancer activity and low intrinsic toxicity. Decursin, a coumarin analogue mainly derived from the roots of the medicinal plant Angelica sinensis, has a wide range of biological activities, including anti-inflammatory, antioxidant, neuroprotective, and especially anticancer activities. Existing studies indicate that decursin affects cell proliferation, apoptosis, autophagy, angiogenesis and metastasis. It also indirectly affects the immune microenvironment and can act as a potential anticancer agent. Decursin can exert synergistic antitumor effects when used in combination with a number of common clinical anticancer drugs, enhancing chemotherapy sensitivity and reversing drug resistance in cancer cells, suggesting that decursin is a good drug combination. Secondly, decursin is also a promising lead compound, and compounds modifying its structure and formulation form also have good anticancer effects. In addition, decursin is not only a key ingredient in several natural herbs and dietary supplements, but is also available through a biosynthetic pathway, with anticancer properties and a high degree of safety in cells, animals, and humans. Thus, it is evident that decursin is a promising natural compound, and its great potential for cancer prevention and treatment needs to be studied and explored in greater depth to support its move from the laboratory to the clinic.